Depressive and anxiety symptoms amid COVID-19 pandemic among healthcare workers in a low-resource setting: a systematic review and meta-analysis from Ethiopia - Kassew, Tilahun; Melkam, Mamaru; Minichil, Woredaw; Wondie, Mesele; Ali, Dawed (Frontiers in Psychiatry, 2024)
Background Coronavirus disease 2019 (COVID-19) outbreak is one of the public health problems that pose a serious mental health concern due to its high morbidity and mortality rate. The healthcare workers are at risk of developing mental health symptoms like depression and anxiety because they are the first point of contact in the diagnosis, treatment, and care of patients with COVID-19. This study aimed to systematically review the prevalence and the associated factors of depression and anxiety disorders among healthcare workers amid COVID-19 pandemic in Ethiopia. Method A systematic review and meta-analysis study was conducted. Different primary studies that assessed the depressive and anxiety disorders during amid COVID-19 pandemic in the Ethiopian healthcare workers were extracted by Microsoft Excel and exported to STATA version 11 for further analysis. Random-effects model meta-analysis was used to the estimate pooled effect size and the effect of each study with their 95% confidence interval. Funnel plot analysis and Egger regression tests were conducted to detect the presence of publication bias. Subgroup analysis and sensitivity analysis were conducted. Results Thirteen studies with 5,174 participants were included in this systematic review and meta-analysis study. The pooled prevalence of depression and anxiety disorders was 40.39% (95% CI: 28.54, 52.24) and 44.93% (95% CI: 31.39, 58.46), respectively. Being a woman, being married, working in the frontline, and having high perceived susceptibility were significantly associated with depression among the Ethiopian healthcare workers. Similarly, being a woman, being older in age, working in the frontline, and having high perceived susceptibility were the factors associated with anxiety disorder among the Ethiopian healthcare workers during the COVID-19 pandemic. Conclusion The prevalence of depression and anxiety disorders in the Ethiopian healthcare workers was high. The timely detection and appropriate management of mental health problems is essential for the quality of healthcare services, and proactive support methods for the female, married, and older-age healthcare professionals could result in these outcomes. Systematic Review Registration https://www.crd.york.ac.uk/PROSPERO/, identifier CRD42022299074.